تقويم كفاءة المنظفات والمطهرات المستخدمة قبل التعقيم للأدوات الجراحية بقسم خدمات التعقيم المركزي بمركز بنغازي الطبي - الصلابي, علاء الدين (Scientific Journal of University of Benghazi, 2021)
This study aimed to evaluate the efficacy of cleaning, disinfection and sterilization products on the provision of sterile surgical instruments and equipment. This study was conducted at the Central Sterilization Service Department of Benghazi Medical Center, by collecting 65 swabs from surgical instruments before and after cleaning, disinfection and sterilization, by using Stabimed, Actoclean perfect, Helipur H Plus and sterilization by steam sterilizers. The swabs were collected and sent to a microbiology laboratory for investigation. The results revealed that using Actoclean as an enzymatic cleaner and disinfectant with a concentration of 4% was more effective than using it as enzymatic alone at 0.5% concentration. The results also demonstrated the efficacy of the cleaning and disinfection of instruments and equipment by using mechanical cleaning followed by enzymatic detergent and high-level disinfection. Furthermore, the results indicated that sterilization after proper cleaning and disinfection using proved concentrations would ensure the best outcomes. The results of the microbiological investigation showed that 16 swabs out of 65 yielded 6 species of bacteria; Acinetobacter spp., Lactobacillus spp., P. aeruginosa, Bacillus spp., E. coli, and Klebsiella spp. Extended Spectrum Beta Lactamase (ESBL) production was observed in E. coli and Klebsiella spp. that were resistant to antibiotics examined. On the other hand, Acinetobacter spp. and P. aeruginosa were also resistant to antibiotics used in antibiotic sensitivity testing.